Expansion of Information Studies (IS) Programme at the University of Dar es Salaam: A Feasibility Study - Nawe, Julita; Materu-Behitsa, Mary M (University of Dar es Salaam Library Journal, 2017)
The objective of this feasibility study was to explore strategies for expanding the Information Studies Programme with a focus on curriculum content and delivery mode. It explored stakeholders ' requirements in terms of curriculum content and delivery modes. Multiple strategies were used to collect data and information. The methods used included review of secondary sources, questionnaires, interviews and focus group discussions. All these methods were triangulated in order to complement each other as each method has its strengths and weaknesses in data collection. Respondents were drawn from 26 institutions. The findings of the study indicated that there is great diversity in skills and knowledge required for professional and career development as information provision services diverge from the traditional four-wall structures. The training needs call for a wider coverage than what is currently provided and the delivery mode also needs diversification. The study recommends that the structure of both the core and optional courses of the current MA programme be revised; postgraduate diploma and taught PhD programmes be introduced and delivery modes be diversified.